Boost pressure influence on combustion, emission characteristics, and performance of diesel engines with various fuel types - Hüseyin Söyler (Engineering Science and Technology, an International Journal)
This study investigates the effects of varying boost pressure levels on engine performance, combustion characteristics, and emissions using different fuel types (diesel, B50, B100) under various engine loads. The results show that increasing boost pressure generally enhances engine performance by raising in-cylinder pressure and heat release rates. For instance, at 75 % engine load, the cylinder pressure increased by 18.7 % for diesel and 15.9 % for B100 when the boost pressure was raised from −20 % to + 20 %. Similarly, combustion efficiency improved, with ignition delay reduced by approximately 4.1 % for diesel and 6.5 % for B100 under the same conditions. However, higher boost pressure also led to increased Brake Specific Fuel Consumption (BSFC), particularly for biodiesel fuels; for B100, BSFC increased from 297.1 g/kWh to 304.95 g/kWh at 50 % engine load. In terms of emissions, higher boost pressure significantly decreased CO and HC emissions by up to 7.5 % and 15.3 %, respectively, for B100. Nevertheless, NOx emissions increased by 5.3 % due to the oxygen content of biodiesel. Soot emissions were notably reduced, with a maximum reduction of 58.4 % observed at 75 % engine load and + 20 % boost pressure for diesel fuel. These findings underscore the need for additional strategies to control NOx emissions, especially for biodiesel applications. In conclusion, optimizing boost pressure is critical for improving engine performance and emissions. Biodiesel and its blends, despite their higher NOx emissions, provide significant environmental benefits due to their cleaner combustion characteristics. This study contributes valuable insights for designing more efficient and sustainable internal combustion engines.